MODEL PENGUKURAN PREFERENSI KONSUMEN MENGGUNAKAN ANALISIS KONJOIN - Supriyanto Supriyanto; Sudjono Sudjono; Idah Rosyidah (Universitas Amikom Purwokerto, 2011)
In the point of view of marketing, problem that frequently happens in designing the product is a conflict of interest between producer and consumer. To over iomi that problems, conjoint analysis can be used. conjoint analysis is a method that is used to measure cowumer preference of a product. By this method, the characteristic of products which consumer like the most can be lonwn. Then can be used bv producir to make a new product or modifi the product. There are two method ii conioint analysb, they are metric and nonmetric conjoint analysis.